The making of transnational social space: Chinese women managing careers and lives between China and Canada. (June 2016) - Shan, Hongxia; Pullman, Ashley; Zhao, Qinghua
China–Canada people flows are increasingly characterized by two-way movement, engendering possibilities and problems, particularly for women juggling careers and lives. Within this context, a qualitative study was conducted to trace the migratory and career trajectories of 15 Chinese migrant women between China and Canada. The study finds that to maximize their career and life spaces, the women endeavored to build and mobilize various forms of capital. Not only did they engage in migratory movement, but some of them also acquired Canadian credentials, moved into entrepreneurship and took up transient jobs. The utility and futility of women's efforts point to "games" of differentiation emanating across fields, particularly along the lines of gender, race and class that were invoked to produce transnational spaces where existing power relations were simultaneously challenged and reaffirmed. Conceptually, this paper is informed by the concept of transnational social field and gender, race and class analysis.